Crop Production Modeling System for Diverse Physiographical Areas in Nueva Vizcaya (Global Journal of Computer Science and Technology, 2022)
The wide range of environmental factors affecting cropping is very difficult to ascertain most especially with the absence of climate monitoring equipment and dissemination of an up-to-date weather data forecasting Due to climate change irregular weather patterns cause major disruptions in agricultural activities and heavy damage to crop yields There is limited data available to anticipate and adapt to climatic changes due to insufficiency of monitoring systems The proposed system entitled Crop Production Modeling System then integrates the use of available state-of-the art climate sensing and monitoring system to gather and interpret data and establish current pattern of weather Portable and unique Field Monitoring Systems FMS installed in strategic locations of the different municipalities of Nueva Vizcaya will be utilize to effectively monitor variations in the weather patterns These weather patterns will be used as a tool to determine the optimal cropping season In addition the system provides different graphical presentations as reports readable and understandable to the users especially to the agricultural sectors Moreover the said system will be accessible and portable to the users in all cases because its internet dependability The present system can be customized to address not only agriculture concerns but also health and safety and disaster and risk management The system has the potential for up scaling and adoption by other provinces or municipalities due to its very promising capabilities
Keywords: crop modeling system; field modeling system; portable; weather pattern; nueva vizcaya